2022
DOI: 10.1186/s13638-022-02153-z
|View full text |Cite
|
Sign up to set email alerts
|

The road to 6G: a comprehensive survey of deep learning applications in cell-free massive MIMO communications systems

Abstract: The fifth generation (5G) of telecommunications networks is currently commercially deployed. One of their core enabling technologies is cellular Massive Multiple-Input-Multiple-Output (M-MIMO) systems. However, future wireless networks are expected to serve a very large number of devices and the current MIMO networks are not scalable, highlighting the need for novel solutions. At this moment, Cell-free Massive MIMO (CF M-MIMO) technology seems to be the most promising idea in this direction. Despite their appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…In summary, this study has demonstrated the value of hardware control and realistic implementations in the context of sensor-actor networks, in addition to offering a fresh approach for mobility optimization. The suggested model is a useful tool for study participants, engineers, and practitioners looking to improve the efficacy and efficiency of sensor-actor networks because it emphasizes practical experimentation and simulation above theoretical frameworks [30] . The future of flexible and receptive networked systems will be greatly influenced by the knowledge gathered from this research, as technology develops and sensor-actor network applications grow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, this study has demonstrated the value of hardware control and realistic implementations in the context of sensor-actor networks, in addition to offering a fresh approach for mobility optimization. The suggested model is a useful tool for study participants, engineers, and practitioners looking to improve the efficacy and efficiency of sensor-actor networks because it emphasizes practical experimentation and simulation above theoretical frameworks [30] . The future of flexible and receptive networked systems will be greatly influenced by the knowledge gathered from this research, as technology develops and sensor-actor network applications grow.…”
Section: Discussionmentioning
confidence: 99%
“…The study examines future trends, challenges, and current research in optimizing resource management. Ijemaru, Li-Minn, and Kah [30] look into swarm intelligence methods for traffic engineering and opportunistic data collection in a smart city waste management through the Internet of Vehicles. While not specifically relevant to sensoractor networks, the research offers valuable perspectives on how to optimize data collection and handling traffic through the use of swarm intelligence.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation